Determination of percentage yield and total phenolic content of ethanol extract from purple passion (Passiflora edulis f. edulis Sims) fruit peel - Sisminnitah Dewi Nofita; Khoirul Ngibad; Achmad Fathoni Rodli (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Free radicals can trigger various diseases, such as cancer, cardiovascular, arthritis, diabetes, neurological disorders, and aging. Thus, antioxidants are needed to reduce these free radicals. The peel of the purple passion fruit (Passiflora edulis f. edulis Sims) has many phenolic compounds that indicate antioxidant capacity. This study aims to determine the percentage yield and total phenolic contents in the ethanol extract of purple passion fruit peel. Extraction of purple passion fruit peel using the method of maceration with ethanol solvent. Measurement of total phenolic levels in ethanol extract from purple passion fruit peel using the UV–Vis Spectrophototometry method with Folin-Ciocalteu reagent. The principle of this method is based on the reagent between gallic acid and the Folin-Ciocalteu reagent that will produce a molybdenum-tungsten complex. Furthermore, the addition of Na2CO3 solution will change the color of the solution to blue, and its absorbance can be measured at a wavelength of 765 nm. The results showed that the ethanol extract from purple passion fruit peel yielded 1.363% and total phenolic levels of 30.758 mg of gallic acid equivalent per the gram of extract. The existence of the total phenolic content proves that the ethanol extract from purple passion fruit peel has the potential to be used as an alternative source of natural antioxidants.